Social Education in Hadith: Building Social Sensitivity and Solidarity among Students - Mutmainnah, Inayatul; Amin, Muhammadiyah; Ahmad, La Ode Ismail (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study examines the importance of social education derived from Hadith in developing students' character as socially responsible individuals rooted in Islamic moral ideals. The research seeks to incorporate the ideals of empathy, solidarity, justice, and compassion, as drawn from Hadith, into educational methodologies. A qualitative methodology was utilized, concentrating on a literature survey and the textual-conceptual analysis of pertinent Hadith. Research indicates that incorporating Hadith-based social ideals into curricula and extracurricular activities, including group debates, simulations, and community service, improves both students' intellectual growth and social consciousness. This study enhances the domain of Islamic education by offering a theoretical and practical framework for the application of Hadith-based social education to tackle modern world issues. This method integrates Islamic ethical ideas with contemporary educational frameworks, promoting comprehensive character development. Future research is advised to assess the long-term effects of these programs across various educational tiers.